Relationship between lexical, reading and spelling skills in bilingual language minority children and their monolingual peers - Vettori, Giulia; Incognito, Oriana; Bigozzi, Lucia; Pinto, Giuliana (Frontiers in Psychology, 2023)
This study was conducted on a population of primary school children including bilingual language minority (BLM) children with L2-Italian and a variety of languages as L1 (e.g., Chinese, Albanian, Latin), and Italian-speaking monolingual children. The variety of languages ecologically reflects the nowadays composition of classes in the Italian school system. The aims were to investigate in both linguistic groups: (1) the developmental patterns of lexical, reading and spelling skills; (2) the pattern of predictive relations between lexical, reading and spelling skills. 159 primary school children from Grade 2 to Grade 5 participated in the study: BLM (n=80) and monolingual (n=79) children aged between 7 and 11 years. Each participant completed a vocabulary task (lexical skills), a text reading task (reading accuracy and reading speed) and a text dictation task (orthographic errors). ANOVA statistics showed the comparison of patterns between monolingual and BLM children in lexical, reading, and writing skills. Results show lower performances in lexical, reading and spelling skills in BLM children learning Italian as a second language compared to monolingual peers. Second, partial correlations performed separately for monolinguals and BLM with lexical ability as a control variable, illustrated that all variables correlated with each other in both groups. This result provides the option of performing hierarchical regressions. Finally, hierarchical regression analyses showed that the pattern of predictive relations between lexical, reading and spelling skills is the same across language groups, with the key role of orthographic accuracy as the pivotal process around which reading and lexical skills are built.